Individual and organizational factors that influence whistle blowing intentions among Malaysian auditors / Khamisah Abd Manaf and Maheran Zakaria - Abd Manaf, Khamisah; Zakaria, Maheran (2021)
Whistleblowing is a disclosure by a member of organisation of any misconduct perpetrated by the management. This noble deed is an effective tool to deter misconducts and hence it is a duty of all parties who stumbled upon such incidences to report to those who can execute actions. Specifically the auditor, although they are abided by the confidentiality rules, their mandatory duty is to whistle blow, should they uncover the misconducts while performing audit work. Indeed, evidences have indicated that numerous misconducts such as mismanagement, misuse of corporate reserves, fraudulent tax evasion, income statement fraud and money laundering were detected through whistleblowing. To date whistleblowing has captured the interests of many studies. Prior studies have indicated that many factors would influence auditors to whistle blow and amongst them are organisational ethical climate, virtue ethics and knowledge of ethics. Emulating previous studies, the objective of this paper is to propose the aforementioned variables namely organizational ethical climate, virtue ethics and knowledge of ethics as the factors that would influence whistleblowing. Hence, the proposed factors are expected to create new possible avenues for future research